The Influence of Motivation and Work Environment on The Performance Employees of Trade and Industrial Department of Gowa District - Andriyani, Lilis; Tawe, Amiruddin; Burhanuddin; Akbar, Abdi; Wardhana Haeruddin, Muhammad Ilham (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of motivation and work environment on employee performance at the Department of Trade and Industry of Gowa Regency. The population in this study were all employees at the Department of Trade and Industry of Gowa Regency, totaling 40 people. The number of samples used is the entire population because there are less than 100 people, namely the type of saturated cover, with this type of quantitative research. The data used are primary data and secondary data obtained using a questionnaire distribution technique.The results of the research after being processed with SPSS. 21 Based on the results of the research it shows that motivation (X1) has a positive and significant effect on employee performance. work environment (X2) has an effect on employee performance, and in terms of positive influence it also has a significant impact. And together motivation and work environment affect employee performance.